2020
DOI: 10.1200/go.20.00107
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Immune Response Markers in Arab Patients With Lung Cancer

Abstract: PURPOSE Programmed death-ligand 1 (PD-L1) is a marker for checkpoint inhibitor use in the management of solid tumors, especially in non–small-cell lung cancer (NSCLC). Our study was aimed at determining the patterns of PD-L1 expression and cluster of differentiation 8 (CD8) immunostains in patients with NSCLC in the Arab population. METHODS Archival tumor tissue from patients with a confirmed diagnosis of NSCLC were obtained and stained for PD-L1 with antibody 22C3, using immunohistochemistry staining and givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…The present study revealed that PD-L1 expression was present in 24.7% of the patients. The prevalence of PD-L1 expression in the present study was similar to data published in the only other study examining PD-L1 expression from our region ( 19 ); however, both studies are corroborated by Dietel et al ( 20 ) in their large multicentre study investigating PD-L1 expression in 18 different countries. PD-L1 positivity did not show a significant association with smoking status, as 27 out of 69 PD-L1-positive patients were non-smokers.…”
Section: Discussionsupporting
confidence: 91%
“…The present study revealed that PD-L1 expression was present in 24.7% of the patients. The prevalence of PD-L1 expression in the present study was similar to data published in the only other study examining PD-L1 expression from our region ( 19 ); however, both studies are corroborated by Dietel et al ( 20 ) in their large multicentre study investigating PD-L1 expression in 18 different countries. PD-L1 positivity did not show a significant association with smoking status, as 27 out of 69 PD-L1-positive patients were non-smokers.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, evaluating PD-L1 expression levels in advanced-stage NSCLC has become a critical aspect of treatment planning. The PD-L1 expression in a lung cancer patient population from the Middle East was found to be similar to published literature ( 10 ).…”
Section: Introductionsupporting
confidence: 85%
“…Besides, EGFR and PDL1 have been proved as predictive biomarkers for tyrosine kinase and PD1/PDL1 inhibitors, respectively, in advanced NSCLC [37,38]. In conjunction with the higher incidence of ADC in the current study, high rates of EGFR mutation and PDL1 overexpression (about 40%) were observed in our patients with NSCLC, in particular in those with ADC [39,40]. This suggests that a large volume of Algerian patients with lung cancer are likely candidates for EGFR-targeted therapy and PD1/PDL1 immunotherapy.…”
Section: Discussionsupporting
confidence: 56%